2007
DOI: 10.3102/0034654307309918
|View full text |Cite
|
Sign up to set email alerts
|

Complicating the Image of Model Minority Success: A Review of Southeast Asian American Education

Abstract: Similar to other Asian American students, Southeast Asian American students are often stereotyped by the popular press as hardworking and high-achieving model minorities. On the other hand, Southeast Asian American youth are also depicted as low-achieving high school dropouts involved in gangs. The realities of academic performance and persistence among Southeast Asian American students are far more complex than either image suggests. This article explores the various explanations for the struggles, successes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
335
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 325 publications
(351 citation statements)
references
References 67 publications
10
335
2
Order By: Relevance
“…As highlighted by Table 1, Southeast Asians are a significantly underrepresented ethnic sub-group, which comprises of people from a variety of Asian ethnic groups from the countries of Vietnam, Laos, and Cambodia (Ngo & Lee, 2007;Teranishi, 2004). They came to the United States in the late 1970s and 1980s as political war refugees, fleeing their home countries as an act of desperation to escape from poverty, torture, and death from the aftermath of the War on Southeast Asia (also known as the Vietnam War) (Ngo & Lee, 2007;Teranishi, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As highlighted by Table 1, Southeast Asians are a significantly underrepresented ethnic sub-group, which comprises of people from a variety of Asian ethnic groups from the countries of Vietnam, Laos, and Cambodia (Ngo & Lee, 2007;Teranishi, 2004). They came to the United States in the late 1970s and 1980s as political war refugees, fleeing their home countries as an act of desperation to escape from poverty, torture, and death from the aftermath of the War on Southeast Asia (also known as the Vietnam War) (Ngo & Lee, 2007;Teranishi, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…They came to the United States in the late 1970s and 1980s as political war refugees, fleeing their home countries as an act of desperation to escape from poverty, torture, and death from the aftermath of the War on Southeast Asia (also known as the Vietnam War) (Ngo & Lee, 2007;Teranishi, 2004). The 2000 U.S. Census showed that 49% of Southeast Asians live in poverty, compared to less than 10% of Japanese and Chinese Americans (Teranishi, 2004), which indicates that the experiences of this specific population is distinct from other AAPIs that have been in the United States for numerous generations.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of Southeast Asian groups studied here, the "model minority myth" commonly held about Asian American children can mask their educational needs, leaving them unmet (Lee, 2001;Ngo & Lee, 2007). Conversely, teachers who understand the tremendous barriers faced by Southeast Asian groups can negatively stereotype these students as "delinquents" and hold lowered expectations for them (Lee, 2001;Trueba et al, 1990).…”
Section: Discussionmentioning
confidence: 91%
“…Yet all groups have some elements in common: examples include a common history related to the Vietnam War; a common experience of resettlement by the U.S. government and granting of assistance afterward; a common experience of prejudiced societal reception; and a common general experience of relegation to manual labor upon entry into the U.S. Additionally, Southeast Asian students into the second generation have continued to struggle in schools; this is even true for many Vietnamese second-generation students who continue to struggle, while another segment thrives, as reflected in their bimodal attainment patterns (Ngo & Lee, 2007;Niedzwiecki & Duong, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation